2010
DOI: 10.1111/j.1600-0625.2010.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of TRPM8 agonists accelerates skin permeability barrier recovery and reduces epidermal proliferation induced by barrier insult: role of cold‐sensitive TRP receptors in epidermal permeability barrier homoeostasis

Abstract: TRPA1 and TRPM8 receptors are activated at low temperature (A1: below 17 degrees C and M8: below 22 degrees C). Recently, we observed that low temperature (below 22 degrees C) induced elevation of intracellular calcium in keratinocytes. Moreover, we demonstrated that topical application of TRPA1 agonists accelerated the recovery of epidermal permeability barrier function after disruption. In this study, we examined the effect of topical application of TRPM8 modulators on epidermal permeability barrier homoeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…The range of thermoactivation of TRPM8 channel fits well with human unprotected skin temperature, +24°C to +33°C (5, 6). Apart from the observation that topical application of TRPM8 chemical agonists can improve epidermal regeneration (16), no solid evidence for the expression of functional TRPM8 in epidermal keratinocytes has been presented yet and no alterations in epidermal homeostasis have been reported in trpm8 −/− null mutant mice suppressing the full-length TRPM8 cold receptor (17,18). However, suppression of the full-length TRPM8 expression does not necessarily affect expression of TRPM8 isoforms (19).…”
Section: •−mentioning
confidence: 99%
“…The range of thermoactivation of TRPM8 channel fits well with human unprotected skin temperature, +24°C to +33°C (5, 6). Apart from the observation that topical application of TRPM8 chemical agonists can improve epidermal regeneration (16), no solid evidence for the expression of functional TRPM8 in epidermal keratinocytes has been presented yet and no alterations in epidermal homeostasis have been reported in trpm8 −/− null mutant mice suppressing the full-length TRPM8 cold receptor (17,18). However, suppression of the full-length TRPM8 expression does not necessarily affect expression of TRPM8 isoforms (19).…”
Section: •−mentioning
confidence: 99%
“…These results suggested that TRPA1 serves as a functional cold-sensitive calcium channel in human epidermal keratinocytes. We also established that TRPM8 was expressed in epidermal keratinocytes, by means of immunohistochemical study and RT-PCR [ 41 ] . Table 6.1 Effects of dry environment (low humidity) on skin pathophysiology Amplifi cation of hyperproliferative response to barrier disruption [ 28 ] Abnormal desquamation of the stratum corneum [ 93 ] Elevation of DNA synthesis in basal layer of the epidermis [ 92 ] Enhancement of barrier function [ 27 ] Appearance of abnormal skin surface morphology [ 94 ] Amplifi cation of allergic reaction [ 55 ] Elevation of IL-1 a mRNA and protein [ 4 ] Amplifi cation of proliferative response induced by surfactant [ 19 ] Decrease of water-holding capacity and free amino acid content in stratum corneum [ 67,94 ] Abrupt decrease in environmental humidity induces abnormalities in barrier homeostasis [ 95 ] Alteration of calcium distribution in epidermis [ 45 ] Increase of mast cell number and histamine content in dermis [ 3 ] Previously, we had found that calcium dynamics was associated with epidermal permeability barrier homeostasis [ 35 ] .…”
Section: Transient Receptor Potential (Trp) Familymentioning
confidence: 99%
“…ß-glucan receptors) present in the intercellular spaces, as shown for an endangerd epidermis like in the capybara (Meyer et al 2008), confirms again the view of a complex barrier biology (Elias 2007). Last but not least, the skin surface temperature may activate or block epidermal barrier homeostasis by temperature sensors (members of the transient receptor potential family), in particular, when the outer temperatures distinctly increase (Denda et al 2007) or decrease (Denda et al 2010). This influence is of some interest for species with no hair coat or with seasonally varying hair coat qualities, but not for otters with a constantly dense fur (Kuhn 2009).…”
Section: Discussionmentioning
confidence: 99%